PELAKSANAAN FUNGSI BALAI BESAR PENGAWASAN OBAT DAN MAKANAN KOTA PONTIANAK - Purba E.01108107, David Agustinus (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this research is the implementation of function and Drug Administration Center for Food Pontianak. This thesis is intended to determine the implementation of the oversight function performed by BBPOM against drug and food distribution facilities in the city of Pontianak , since there are still many drugs and food products that contain chemicals, drugs (BKO) , illegal , and expired circulating in the community. The method used in this paper is to use qualitative methods with descriptive research. In this study conducted supervision includes direct supervision and indirect supervision of the drug and food distribution facilities that sell drugs and food products in Pontianak. Results of data analysis showed that the surveillance conducted by BBPOM Pontianak is still weak due to the inadequate number of employees, which is less strict legal sanctions and lightweight, and a low degree of public knowledge about the dangers of a product containing chemicals, drugs (BKO), illegal and expired. Therefore, in order to optimize the function of oversight BBPOM Pontianak necessary increase in staff numbers, provide strict legal sanctions for dealers and sellers of food and drug products that are not in accordance with the standards of quality, safety, and efficacy of a product, and increased socialization of product hazards drugs and foods that contain chemicals, drugs (BKO), illegal and expired.Â Keywords: BBPOM, Means of Distribution, Direct Supervision, Indirect Supervision.